Association of Dickkopf-1 Polymorphisms with radiological damage and periodontal disease in patients with early rheumatoid arthritis: a cross-sectional study (2020)
Background Rheumatoid arthritis (RA) is a systemic autoimmune disease that increased bone resorption. Periodontal disease (PD) is an associated risk factor of RA. Studies suggest an association between bone markers such as the dickkopf-related protein 1 (DKK-1) and progression of radiological damage. We aimed to evaluate the marker DKK-1, its polymorphisms in patients with early rheumatoid arthritis (eRA), and its association with rheumatic, radiological, and periodontal variables. Methods This is a cross-sectional study. Samples were obtained from 63 patients with eRA. Radiographs of hands and feet were evaluated by Sharp–van der Heijde score (SHS) and Simple Erosion Narrowing Score (SENS). Serum DKK-1 levels and high-resolution fusion analysis was used for polymorphisms (rs1896368, rs1896367, rs1528873). Bivariate analyses were performed. Results Individuals heterozygous for rs1896367 had more frequent erosions (p = 0.026) and joint space narrowing (p = 0.005) in the feet, higher SHS (p = 0.016), and higher SENS (p ≤ 0.001). Patients homozygous for rs1896368 had less frequent joint space narrowing in hands and feet as assessed by SHS and less presence of erosions by SENS (odds ratio, 0.04; 95% confidence interval, 0.00–0.93; p < 0.05). The presence of PD was associated with the homozygous of rs1896367 (p = 0.009) and the heterozygous of rs1896368 (p = 0.033). Conclusions Polymorphism rs1896367 seems to be associated with greater radiological compromise; rs1896368 confers protection against bone damage in Colombian eRA patients.